Barriers Experienced by First Nations Deaf People in the Justice System - Elder, Brent; Soldatic, Karen; Schwartz, Michael A; Barney, Jody; Howard, Damien; McGee, Patrick (Journal of Deaf Studies and Deaf Education, 2024)
Anecdotal evidence strongly suggests that members of the First Nations Deaf community experience more barriers when engaging with the criminal justice system than those who are not deaf. Therefore, our purpose for writing this article is to highlight legal and policy issues related to First Nations Deaf people, including perspectives of professionals working with these communities, living in Australia who have difficulty in accessing supports within the criminal justice system. In this article, we present data from semi-structured qualitative interviews focused on four key themes: (a) indefinite detention and unfit to plead, (b) a need for an intersectional approach to justice, (c) applying the maximum extent of the law while minimizing social services–related resources, and (d) the need for language access and qualified sign language interpreters. Through this article and the related larger sustaining project, we seek to center the experiences and needs of First Nations Deaf communities to render supports for fair, just, and equitable access in the Australian criminal justice system to this historically marginalized group.